PATOLOGIA DA POLIEDROSE NUCLEAR DO CURUQUERÊ DO ALGODÃO Alabama argillacea (HUBNER. 1818) (LEP., NOCTUIDAE) - Andrade, C. F. S.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2015)
PATOLOGIA DA POLIEDROSE NUCLEAR DO CURUQUERÊ DO ALGODÃO Alabama argillacea (HUBNER. 1818) (LEP., NOCTUIDAE)